2015
DOI: 10.1007/s13199-015-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Root-inhabiting fungi in alien plant species in relation to invasion status and soil chemical properties

Abstract: In order to recognize interactions between alien vascular plants and soil microorganisms and thus better understand the mechanisms of plant invasions, we examined the mycorrhizal status, arbuscular mycorrhizal fungi (AMF) colonization rate, arbuscular mycorrhiza (AM) morphology and presence of fungal root endophytes in 37 non-native species in Central Europe. We also studied the AMF diversity and chemical properties of soils from under these species. The plant and soil materials were collected in southern Pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
(103 reference statements)
2
27
1
3
Order By: Relevance
“…As revealed by our study, soil properties (e.g., soil pH, total organic carbon, total nitrogen, and available P) were higher in the EXO soils compared with the NAT soils. These results are in agreement with previous work (Soumare et al 2015;Majewska et al 2015) that reported higher values of soil pH and available P in the root zone of invasive exotic plants, such as Acacia senegal, Acacia seyal, Acacia albida, Eragrostis albensis, and Olpidium spp. By altering the chemical properties of the soil below their canopy, invasive plant species may alter the nutrient cycle (Follstad Shah et al 2010) and thus may be responsible for the modification AMF community composition in the EXO soils (Zubek et al 2016;Zubek et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…As revealed by our study, soil properties (e.g., soil pH, total organic carbon, total nitrogen, and available P) were higher in the EXO soils compared with the NAT soils. These results are in agreement with previous work (Soumare et al 2015;Majewska et al 2015) that reported higher values of soil pH and available P in the root zone of invasive exotic plants, such as Acacia senegal, Acacia seyal, Acacia albida, Eragrostis albensis, and Olpidium spp. By altering the chemical properties of the soil below their canopy, invasive plant species may alter the nutrient cycle (Follstad Shah et al 2010) and thus may be responsible for the modification AMF community composition in the EXO soils (Zubek et al 2016;Zubek et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to studies where a high proportion of dual colonization of AM and DSE fungi in roots of plant species examined have been reported (Massenssini et al 2014;Majewska et al 2015). Our observation of a negative correlation between %RLTC and %RLDTC is in agreement with studies where an inverse relationship between these fungal variables has been reported (Muthukumar et al 2006;Mandyam & Jumpponen 2008;Muthukumar & Tamilselvi 2010).…”
Section: Relationship Between Am and Dse Fungisupporting
confidence: 92%
“…plants change the abundance, diversity, and structure of plant and animal communities (Hejda et al 2009;Lenda et al 2013), and often considerably modify physicochemical and biological properties of the soil environment, thereby potentially affecting key ecosystem processes (Vilà et al 2011;Castro-Díez et al 2014;Majewska et al 2015;Stefanowicz et al 2016;Zubek et al 2016;Broadbent et al 2017;CastroDíez and Alonso 2017;Lavoie 2017;Rodríguez-Caballero et al 2017).…”
Section: Introductionmentioning
confidence: 99%